Mitochondrial DNA and Epigenetics: Investigating Interactions with the One-Carbon Metabolism in Obesity - Bordoni, Laura; Petracci, Irene; Mlodzik-Czyzewska, Monika; Malinowska, Anna M.; Szwengiel, Artur; Sadowski, Marcin; Gabbianelli, Rosita; Chmurzynska, Agata (Oxidative medicine and cellular longevity, 2022)
Mitochondrial DNA copy number (mtDNAcn) has been proposed for use as a surrogate biomarker of mitochondrial health, and evidence suggests that mtDNA might be methylated. Intermediates of the one-carbon cycle (1CC), which is duplicated in the cytoplasm and mitochondria, have a major role in modulating the impact of diet on the epigenome. Moreover, epigenetic pathways and the redox system are linked by the metabolism of glutathione (GSH). In a cohort of 101 normal-weight and 97 overweight/obese subjects, we evaluated mtDNAcn and methylation levels in both mitochondrial and nuclear areas to test the association of these marks with body weight, metabolic profile, and availability of 1CC intermediates associated with diet. Body composition was associated with 1CC intermediate availability. Reduced levels of GSH were measured in the overweight/obese group (p=1.3∗10−5). A high BMI was associated with lower LINE-1 (p=0.004) and nominally lower methylenetetrahydrofolate reductase (MTHFR) gene methylation (p=0.047). mtDNAcn was lower in overweight/obese subjects (p=0.004) and independently correlated with MTHFR methylation levels (p=0.005) but not to LINE-1 methylation levels (p=0.086). DNA methylation has been detected in the light strand but not in the heavy strand of the mtDNA. Although mtDNA methylation in the light strand did not differ between overweight/obese and normal-weight subjects, it was nominally correlated with homocysteine levels (p=0.035) and MTHFR methylation (p=0.033). This evidence suggests that increased body weight might perturb mitochondrial-nuclear homeostasis affecting the availability of nutrients acting as intermediates of the one-carbon cycle.